2024
DOI: 10.3390/ma17102206
|View full text |Cite
|
Sign up to set email alerts
|

Role of Woody Biomass Ash Material in Immobilization of Cadmium, Lead and Zinc in Soil

Elżbieta Rolka,
Mirosław Wyszkowski,
Andrzej Cezary Żołnowski
et al.

Abstract: Nowadays, we have observed the dynamic development of bio-heating plants that use wood biomass for heating or energy purposes. The result of this process is a reduction in carbon dioxide emissions as well as in the production of biomass ash (BA). Despite the waste nature of BA, it should be carefully analyzed and assessed for various applications, including environmental ones. Due to the features attributed to BA, including its alkaline reaction, the high capacity of its sorption complex, relatively low salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…First of all, the positive effects of soil treatment with ash on EBC, HAC, CEC, and BS were noted in the studies by An and Park [74] as well as Meller and Bilenda [75]. Rolka et al [76,77] used ash from the combustion of mixed wood chips, mainly Scots pine (Pinus sylvestris L.), and, similar to our own research, a positive effect of wood ash on the soil properties was observed. Meller and Bilenda [75] showed that soil fertilization with ash increased the soil's EBC and BS and decreased HAC.…”
Section: Response Of Soil Enzymes and Certain Chemical And Physicoche...supporting
confidence: 82%
“…First of all, the positive effects of soil treatment with ash on EBC, HAC, CEC, and BS were noted in the studies by An and Park [74] as well as Meller and Bilenda [75]. Rolka et al [76,77] used ash from the combustion of mixed wood chips, mainly Scots pine (Pinus sylvestris L.), and, similar to our own research, a positive effect of wood ash on the soil properties was observed. Meller and Bilenda [75] showed that soil fertilization with ash increased the soil's EBC and BS and decreased HAC.…”
Section: Response Of Soil Enzymes and Certain Chemical And Physicoche...supporting
confidence: 82%